Normativitas Pegadaian Syariah dan Praktiknya di Dunia Muslim - Ali Murtadho (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2021)
The existence of pawnshops appears to respond to urgent funding needs, especially for weak economies. Compared to banks or other financial institutions, pawnshops have their own advantages that are relatively easy for those who need funds quickly. However, even though it has a social nuance with relatively small capital rent (interest), conventional pawnshops are still considered problematic from the perspective of interest-free Islamic economic law. This problem gave rise to syari'ah pawnshops which eliminated the interest / capital lease system. In order to earn income for the institution as a substitute for interest, pawnshops syari'ah adopt contracts in muamalah fiqh that are formally seen as allowing the collection of fees from customers, for example the wadi'ah contract, ijarah, bai 'muqayadlah, and so on. The practical interpretation of the Shari'ah pawning formula in Muslim countries is quite varied, which is influenced by various factors not only due to the religiousness of the community but also to the economic and cultural conditions of the community.Keywords : Sharia Pawnshop, Capital Lease, and Ujrah.